Cloud technologies of augmented reality as a means of supporting educational and research activities in chemistry for 11th grade students - Pavlo P. Nechypurenko; Serhiy O. Semerikov; Olesia Yu. Pokhliestova (Academy of Cognitive and Natural Sciences, 2023)
Chemistry educational and research activities must be planned in a way that makes extensive use of experimentation. The implementation of chemistry experiments in the classroom is fraught with organizational and logistical challenges, and more recently, the necessity for online learning has been added. The article explains the current state of augmented reality (AR) technology use in contemporary chemical education and the potential for using augmented reality technology to enhance students' chemistry research projects. To complete the research tasks, augmented reality cloud technologies (A-Frame and AR.js) were used. The developed tool is a virtual chemical laboratory that incorporates augmented reality technologies (AR-based virtual chemical laboratory): individual markers correspond to reagents, and a pair of marker combinations activates the playback of a video showing the chemical interaction between the associated pair of reagents. The article describes the development of augmented reality software to support the research activities of 11th grade chemistry students in the form of an AR-based virtual chemical laboratory, as well as its implementation in the teaching and learning process.